A new approach on the regulation of NF-κB and Bax protein signaling pathway activation by royal jelly in fluoride-induced pancreas damage in rats. (December 2022) - Aslan, Abdullah; Can, Muhammed Ismail; Beyaz, Seda; Gok, Ozlem; Parlak, Gozde; Gundogdu, Ramazan; Ozercan, Ibrahim Hanifi; Erman, Orhan
Abstract: Forty-two healthy adult male rats (Wistar albino, n = 42, 8 weeks old, starting weights 200–250 g) employed in this study were subdivided into six groups randomly with seven rats per group as follows: (i) Control group: received standard diet; (ii) RJ group: received standard diet supplemented with royal jelly; (iii) F50 group: received standard diet supplemented with fluoride (50 mg/kg BW); (iv) F100 group: received standard diet supplemented with fluoride (100 mg/kg BW); (v) F50 +RJ group: received standard diet supplemented with fluoride (50 mg/kg BW) and royal jelly; (iv) F100 +RJ group: received standard diet supplemented with fluoride (100 mg/kg BW) and royal jelly. The study continued for a total of eight weeks. Western blot analysis was conducted to determine the post-translational expression levels of NF-κB, Bax, Bcl-2, TNF-α, Caspase-3 and Caspase-6 proteins in pancreas tissue. The pancreatic tissue was subjected to histopathological evaluation. Furthermore, MDA, GSH and CAT activities were examined by spectrophotometric analyzes. Our findings demonstrate that, compared to the control and RJ groups, Bcl-2 protein expression was augmented and, conversely, Caspase-6, Caspase-3 and Bax protein levels were decreased upon fluoride treatment. A statistically significant increase in TNF-α and NF-κB protein expressions was observed in the groups with fluoride-induced damage compared to the control and RJ groups. The MDA levels were increased in all fluoride-treated rats compared to those in the control and RJ groups, whereas the CAT and GSH activities were reduced in all rats with fluoride- induced damage. Although there was not a great difference between the groups regarding histopathological findings, there was a tendency to decrease in the rate of damage upon royal jelly treatment. Highlights: Royal jelly (RJ) protects pancreas tissue against fluoride induced pancreas damage. RJ up-regulates the expression of Bax, caspase-3 and caspase-6, down-regulates the expression of NF-κB, Bcl-2 and TNF-α proteins. RJ increases GSH level, CAT activity and decreases MDA level in pancreas damage.